2019
DOI: 10.21608/puj.2019.10650.1035
|View full text |Cite
|
Sign up to set email alerts
|

Potent lethal effect of Syzygium aromaticum essential oil on Blastocystis spp.: An in vitro study

Abstract: Blastocystis spp. are protozoan inhabiting the gastrointestinal tract, with an incidence usually reaching 5% in developed countries, exceeding 40% in individuals with chronic gastrointestinal illness, and can reach up 76% in developing countries [1,2]. Infection with Blastocystis spp. can be detected in stool samples of asymptomatic individuals or patients complaining of diarrhea [3]. However, as the data depend on methods used for diagnosis, blastocystosis is likely underestimated [4]. Currently, Blastocystis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The results of this study in accordance, with Ueda-Nakamura et al, [20] who observed 100% inhibition of Leishmania amazonensis with the concentration of 100 μg/ml. In a study conducted by Hayam M Ezz Eldin [21], a significant inhibition of 95.1% was observed with concentration of 100 mg/ml after 24 h, which also progressed to complete inhibition (100%) after 72hours of treatment. In addition, the anthelminthic activity of the EJUA-BA | March 2023 eugenol of Syzygium aromaticum against the fish parasite Gyrodactylus sp.…”
Section: Figmentioning
confidence: 96%
See 1 more Smart Citation
“…The results of this study in accordance, with Ueda-Nakamura et al, [20] who observed 100% inhibition of Leishmania amazonensis with the concentration of 100 μg/ml. In a study conducted by Hayam M Ezz Eldin [21], a significant inhibition of 95.1% was observed with concentration of 100 mg/ml after 24 h, which also progressed to complete inhibition (100%) after 72hours of treatment. In addition, the anthelminthic activity of the EJUA-BA | March 2023 eugenol of Syzygium aromaticum against the fish parasite Gyrodactylus sp.…”
Section: Figmentioning
confidence: 96%
“…They indicate a similar mode of action of the clove on helminths as with some anthelminthic drugs [21,[29][30][31][32].…”
Section: Figmentioning
confidence: 99%